Analisis Determinan Intensitas Perilaku Wajib Pajak dalam Menggunakan E-Filing pada KPP Pratama Kisaran - Nurhadika; Alistraja Dison Silalahi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of the Intensity Determinants of Individual Taxpayers in Using E-Filling at KPP Pratama Kisaran North Sumatra, to examine and analyze the effect of perceived benefits, convenience, experience and information technology innovation on behavioral intensity in the use of e-filing. The sample of the research population can use the Slovin formula with 100 respondents consisting of taxpayers at KPP Pratama Kisaran. The results of the test using SPSS showed that the perception of benefits had a positive effect on the behavioral intention of taxpayers to use e-filling, the perception of convenience had a positive effect on the behavioral intentions of taxpayers to use e-filling, the perception of experience had a positive effect on the behavioral intentions of taxpayers to use e-filling. , the perception of information technology innovation has a positive effect on the behavioral intention of taxpayers to use e-filling. The level of influence of perceived benefits, convenience, experience and information technology innovation on the behavioral intention of taxpayers in using e-filling is 0.496. From the results of the calculation of the coefficient of determination, it can be explained that perceptions of benefits, convenience, experience and information technology innovation have a 50% effect on intentions. using e-filling and while 50% is influenced by other factors that are outside of this research.